Verbal fluency as a screening tool for mild cognitive impairment. (1st September 2020) - McDonnell, Michelle; Dill, Lauren; Panos, Stella; Amano, Stacy; Brown, Warren; Giurgius, Shadee; Small, Gary; Miller, Karen
ABSTRACT: Objectives: The goal of this study was to evaluate the ability of semantic (animal naming) and phonemic (FAS) fluency in their ability to discriminate between normal aging, amnestic-Mild Cognitive Impairment (a-MCI), and Alzheimer's disease (AD). Design: We used binary logistic regressions, multinomial regressions, and discriminant analysis to evaluate the predictive value of semantic and phonemic fluency in regards to specific diagnostic classifications. Setting: Outpatient geriatric neuropsychology clinic. Participants: 232 participants (normal aging = 99, a-MCI = 90, AD = 43; mean age = 65.75 years). Measurements: Mini-mental State Examination (MMSE), Controlled Oral Word Association Test Results: Results indicate that semantic and phonemic fluency were significant predictors of diagnostic classification, and semantic fluency explained a greater amount of the discriminant ability of the model. Conclusions: These results suggest that verbal fluency, particularly semantic fluency, may be an accurate and efficient tool in screening for early dementia in time-limited medical settings.